2021
DOI: 10.1111/ejn.15137
|View full text |Cite
|
Sign up to set email alerts
|

Persistent increases of PKMζ in memory‐activated neurons trace LTP maintenance during spatial long‐term memory storage

Abstract: PKMζ is an autonomously active PKC isoform crucial for the maintenance of synaptic long-term potentiation (LTP) and long-term memory. Unlike other kinases that are transiently stimulated by second messengers, PKMζ is persistently activated through sustained increases in protein expression of the kinase. Therefore, visualizing increases in PKMζ expression during long-term memory storage might reveal the sites of its persistent action and thus the location of memory-associated LTP maintenance in the brain. Using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 70 publications
(140 reference statements)
2
12
0
Order By: Relevance
“…The CCT-induced, persistent changes in entorhinal-hippocampus circuit function demonstrate that appropriately structured cognitive experiences can persistently change information processing within neural subcircuits. As such, the present findings strongly support the neuroplasticity hypothesis, although of course, CCT causes additional changes 14,17,47 , with others yet to be discovered. Prior work showed that preemptive CCT in adolescence prevented cognitive impairment due to neonatal neurodevelopmental brain damage 48 , and as also demonstrated here, mere place learning was not sufficient to cause several neurobiological changes that CCT causes.…”
Section: An Entorhinal-hippocampal Subcircuit Tuned By Cognitive Control Trainingsupporting
confidence: 89%
See 2 more Smart Citations
“…The CCT-induced, persistent changes in entorhinal-hippocampus circuit function demonstrate that appropriately structured cognitive experiences can persistently change information processing within neural subcircuits. As such, the present findings strongly support the neuroplasticity hypothesis, although of course, CCT causes additional changes 14,17,47 , with others yet to be discovered. Prior work showed that preemptive CCT in adolescence prevented cognitive impairment due to neonatal neurodevelopmental brain damage 48 , and as also demonstrated here, mere place learning was not sufficient to cause several neurobiological changes that CCT causes.…”
Section: An Entorhinal-hippocampal Subcircuit Tuned By Cognitive Control Trainingsupporting
confidence: 89%
“…This neural network motif will also stabilize the connection's inputoutput relationship 37,38 . Similar disinhibitory plasticity has also been described at the Schaffer collateral and other cortical synapses [39][40][41] , where CCT causes persistent increased expression of PKMz, which is itself necessary and sufficient for maintaining LTP 17,42 . The CCT-induced subcircuit changes were detected in field potential recordings, indicating they are not the sparse changes that mediate content-specific memory formation that the synaptic plasticity and memory hypothesis predicts 43 .…”
Section: An Entorhinal-hippocampal Subcircuit Tuned By Cognitive Control Trainingsupporting
confidence: 55%
See 1 more Smart Citation
“…We have argued that such a switch is most likely implemented at the level of translation, and that the synthesized protein that potentiates synaptic transmission is PKM ζ . The approach we take is based on the observation that its synthesis is likely local in dendrites and perhaps spines ( Muslimov et al, 2004 ; Westmark et al, 2010 ; Palida et al, 2015 ), and that the induction of L-LTP results in a local and sustained increase of PKM ζ in spines ( Hsieh et al, 2021 ). The synthesis of a specific protein (for example, PKM ζ ) could affect its own level of translation, and this positive feedback loop can generate bistable or multstable switches ( Westmark et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Once synthesized in response to synaptic stimulation, the kinase PKMζ remains persistently active in the absence of further stimuli, which is key to the maintenance of LTP (Sacktor & Fenton, 2018). Here, Hsieh et al (2021) use quantitative immunohistochemistry to study the upregulation of PKMζ in synapses encoding active place avoidance. PKMζ levels increase for at least a month and increases with neurons in the CA1, where the Arc promotor was activated.…”
Section: Identifying the Players: The Proteins Of Memorymentioning
confidence: 99%